Fe/ZSM-5-catalyzed-synthesis of 1,4-dihydropyridines under ultrasound irradiation and their antioxidant activities - Sutarni, Yayan Dwi; Purwono, Bambang; Kunarti, Eko Sri; Mardjan, Muhammad Idham Darussalam (Universiti Kebangsaan Malaysia, 2023)
A small library of 1,4-dihydropyridines have been synthesized from ethyl acetoacetate, ammonium acetate and various aldehydes via Hantzsch multicomponent reaction in the presence of Fe/ZSM-5 catalyst under ultrasound irradiation for 90 min. 1,4-Dihydropyridine derivatives were obtained in 64-86% yields and the heterogeneous Fe/ZSM-5 catalyst can be employed for four reaction cycles without losing the catalytic activity. All products were evaluated for their antioxidant activities using the DPPH method and compound 4g was found to be an effective antioxidant agent with DPPH activity of 83.5%.